The Effectiveness of Web-Based Assessment on Student’s Understanding of Concepts on Equilibrium and Rotation Dynamics - Neng Dyah Surya Pratama (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2020)
This study aims to determine the effectiveness of using a web-based assessment on students’ conceptual understanding of equilibrium and rotation dynamics. The method of collecting data using a quasi-experimental design with an experimental procedure is One-Group-Pretest-Posttest Design. The data analysis technique used descriptive statistical calculations in pretest, posttest, and N-gain scores. Besides, using different test paired sample t-test, effect size, and g-factor. The results other the pair results ed-sample t test showed-test the use of web-based assessment had a very large effect on students’ mastery of concepts as indicated by the difference in the pretest and posttest scores. With the g-factor, there is the effectiveness of learning using a web-based assessment, and there is an increase in scores due to treatment, and students’ initial ability does not influence it. With a correlation test for pretest and N-gain scores and a correlation test for pretest and posttest scores, web-based assessment effectively facilitates all students.